Benefits of Inclusive Classrooms for All Primary Students (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Inclusive education is widely recognized as an important foundation of modern schooling, ensuring equal access and participation for all children, including those with disabilities and diverse learning needs. This article discusses the multiple benefits of inclusive classrooms for primary school students, based on current literature and reflective analysis. It shows how inclusive practices support not only students with special needs but also typically developing children by fostering positive attitudes, improving social skills, and enhancing academic outcomes. The article argues that effective inclusion relies on skilled teachers, supportive leadership, and a school culture that values diversity and equity.